2001
DOI: 10.1007/s004410100370
|View full text |Cite
|
Sign up to set email alerts
|

The spinal nerves innervate putative chemosensory cells in the ventral skin of desert toads, Bufo alvarius

Abstract: Toads normally obtain water by absorption across their skin from osmotically dilute sources. When hyperosmotic salt solutions are presented as a hydration source to dehydrated desert toads, they place the ventral skin onto the source but soon afterwards escape to avoid dehydration. The escape behavior coincides with neural excitation of the spinal nerves that innervate putative chemosensory cells in the ventral skin. In the present study, fluorescent dye translocated through the spinal nerves to those receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The integument of anuran amphibians is basically formed by an epidermal and a dermal layer, and as amphibia occur in a wide spectrum of different habitats, the integument performs several functions such as mechanical protection (Farquhar and Palade, 1965;Fox, 1986a,b), chemical defense (Bueno et al, 1981;Delfino et al, 1995), sensory perception (Mearow and Diamond, 1988;Koyama et al, 2001), ionic transportation (Sullivan et al, 2000), water absorption (Hoffman and Katz, 1999;Sullivan et al, 2000), respiration (Duellman and Trueb, 1994), and osmoregulation (Bentley and Yorio, 1976).…”
Section: Introductionmentioning
confidence: 98%
“…The integument of anuran amphibians is basically formed by an epidermal and a dermal layer, and as amphibia occur in a wide spectrum of different habitats, the integument performs several functions such as mechanical protection (Farquhar and Palade, 1965;Fox, 1986a,b), chemical defense (Bueno et al, 1981;Delfino et al, 1995), sensory perception (Mearow and Diamond, 1988;Koyama et al, 2001), ionic transportation (Sullivan et al, 2000), water absorption (Hoffman and Katz, 1999;Sullivan et al, 2000), respiration (Duellman and Trueb, 1994), and osmoregulation (Bentley and Yorio, 1976).…”
Section: Introductionmentioning
confidence: 98%
“…Thereafter, a number of contributions have revealed diverse traits of ventral skin morphology that differ among species and affect water uptake, such as thickness, sculpturing, presence of verruca hidrophilica (protrusions that increase surface area and characterize the ventral integument of many anuran amphibians), or increased capillary bedding [5]. Furthermore, the ventral skin of some anurans have chemosensory properties and can detect salts, helping individuals to avoid hyper-osmotic sources of water [18].…”
Section: Skin Morphology and Water Balancementioning
confidence: 99%
“…Subsequently, studies have reported putative SCCs on the barbels and nasopharynx of hagfish (Braun, , ; Braun & Northcutt, ), on the skin surface of brook lampreys ( Lampetra planeri Bloch) and river lampreys ( Lampetra fluviatilis L.), including the oral, gill pore, dorsal fin and genital regions (Baatrup & Døving, ; Fox, Lane, & Whitear, ; Whitear & Lane, ), on the skin, gills, and oropharynx of chondrichthyes and bony fish (Codina et al, ; Hansen, Ghosal, Caprio, Claus, & Sorensen, ; Kotrschal, ; Kotrschal, Krautgartner, & Hansen, ; Kotrschal, Peters, & Atema, ; Kotrschal, Whitear, & Adam, ; Kuciel et al, ; Peach, ; Peters, Kotrschal, & Krautgartner, ; Peters, Van Steenderen, & Kotrschal, ; Silver & Finger, ; Whitear & Moate, ). Other studies have described SCCs on the skin and in the oral cavity of amphibians (Koyama, Nagai, Takeuchi, & Hillyard, ; Nagai, Koyama, Von Seckendorff Hoff, & Hillyard, ; Osculati & Sbarbati, ; Whitear, ), and in the airways of reptiles and mammals (Finger et al, ; Hansen, ; Saunders, Christensen, Finger, & Tizzano, ; Sbarbati, Crescimanno, Benati, & Osculati, ; Sbarbati, Crescimanno, Bernardi, & Osculati, ; Sbarbati & Osculati, ; Tizzano et al, ; Tizzano, Merigo, & Sbarbati, ). The study of SCC innervation and physiology has been challenging because of the scarcity and widespread distribution of these cells.…”
Section: Introductionmentioning
confidence: 96%